The Values of Honesty and Discipline in Character Education for Early Childhood - Annisa Ledi Astuti; Hamengkubuwono; M.Iqbal Liayong Pratama (International Journal of Innovation and Education Research, 2023)
If character formation is already wrong, it will have an impact on the character of children in the future. Character education is a system of instilling character values that includes knowledge components. This research aims to find out how the value of honesty and discipline in character education for early childhood according to Ki Hajar Dewantara. The type of research used is library research. This research is conducted by a series of collecting, processing and analyzing data taken from written literature, so that it is clear about the values of honesty and discipline in early childhood according to Ki Hajar Dewantara. The results of the study The values of honesty and discipline in character education for early childhood according to Ki Hajar Dewantara are three pillars, namely Ing ngarso sung tuladha, Ing madya mangun karsa and Tut wuri handayani. From these three mottos, there are values of honesty and discipline in it, namely: Responsibility, being kind, trustworthy, fostering order, keeping promises, always telling the truth, fostering an obedient attitude, always on time, and independent